PENGARUH DISIPLIN KERJA, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KARYAWAN - Mariska, Lely (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2025)
This research employs a quantitative approach. The sample size used in this study consists of 35 respondents. The data collection method employed was a questionnaire distributed to employees of PT. Candi Ngrimbi Belerang Unit 1  Tamansari Branch, Banyuwangi, which had been tested for validity and reliability. The collected data were analyzed using multiple linear regression analysis, T-test,  F-test, and ANOVA, supported by SPSS 25 (Statistical Product and Service Solution) software. The results of the study indicate that work discipline has a partial influence on job satisfaction among employees of PT. Candi Ngrimbi Belerang Unit 1 Tamansari Branch, Banyuwangi. Additionally, it was found that  compensation does not partially influence job satisfaction among employees of PT. Candi Ngrimbi Belerang Unit 1 Tamansari Branch, Banyuwangi. Furthermore, the  work environment does not partially affect job satisfaction among employees of PT. Candi Ngrimbi Belerang Unit 1 Tamansari Branch, Banyuwangi.